To compare the efficacy and safety of intravaginal misoprostol and intracervica lcervigel for induction of labour - Malik, Nivedita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This randomized prospective study was conducted in the department of obstetrics and Gynaecology Batra Hospital and Medical Research centre from 1st March to 30th April 2008 to compare the safety and efficacy of intravaginal misoprostol and intracervical dinoprostone gel (cervigel) for cervical ripening and induction of labour. Methods: 80 women were recruited in the study. 40 women were administered misoprostol tablet 25ug vaginally while the other 40 were given intracervical cervigel. Results: A total of 85.1% (68 patients) delivered vaginally (33 in the misoprostol group and 35 in the cervigel group) i.e. spontaneous vaginal and assisted vaginal deliveries. The mean interval from start of induction to vaginal delivery was 707.63+146.511 minutes in the misoprostol group and 833.13 +144.36 minutes in the cervigel group with p=0.001 which was significant statistically. Though both the groups showed a favourable change in Bishop’s score after induction but this was not statistically significant. However, the number of doses required in both the groups to produce an effect on cervical ripening and dilation was statistically significant p=0.001, cervigel group requiring lesser dose (42.5% in cervigel vesus 7.5% in the misoprostol group after administration of 1st dose). Conclusions: Both 25ug misoprostol intravaginal and dinoprostone gel intracervical are equally effective and safe for cervical ripening and induction of labour.